From Border to Headline: Linguistic Patterns and Rhetorical Devices in English News Headlines of the Thailand–Cambodia Conflict - Pantakod, Panuwat; Panomsert, Teetima; Ariyatugun , Khanuengnit; Pongkaew , Supasuda (Journal for Developing the Social and Community, 2025)
Background and Aims: The English-language media in Thailand produces political and diplomatic news content to shape reader perceptions of events while forming their ideological beliefs. The headlines create emotional and cognitive engagement by using specific linguistic patterns and rhetorical devices. The research has two main objectives which aim (1) to identify the frequency of linguistic patterns and rhetorical devices employed in headlines across a sample of media outlets and (2) to analyze the ways in which these linguistic patterns and rhetorical devices contribute to making headlines attention-grabbing and persuasive. Methodology: This study analyzed 120 political and diplomatic news headlines, purposively selected from four English-language Thai news sources (The Nation, Bangkok Post, Khaosod English, Thai Enquirer) published between June and August 2025. The research used Mixed-Methods methodology which combined quantitative pattern detection methods with qualitative evaluation techniques to study how language elements create attention-grabbing headlines that affect readers. Results: The research findings reveal that Framing Effects were the most common linguistic pattern, appearing in 40.83% of instances, followed closely by Emotional Language. These strategies highlight how information was framed and evoked emotional responses to shape readers’ perceptions. Other persuasive elements such as social influence, attention-grabbing devices, and stereotypes or biases appeared less frequently but still contributed to the overall impact. Regarding rhetorical devices, Pathos was the most dominant, occurring in 19.17% of cases, supported by Ethos and Logos. Conclusion: The use of linguistic patterns and rhetorical devices in conflict-related headlines significantly influences readers’ interpretations, shapes meaning, and reinforces ideological polarization within media discourse.